Номер 54

При якому значенні змінної:
1) вирази 6 – (2x – 9) і (18 + 2x) – 3 (x – 3) набувають рівних значень;
2) значення виразу –4 (2y – 0,9) на 2,4 менше від значення виразу 5,6 – 10y?

1) 6 – (2x – 9) = (18 + 2x) – 3(x – 3);
6 – 2x + 9 = 18 + 2x – 3x + 9;
–2x + x = 27 – 15;
x = 12;
x = –12.

Відповідь: –12.

2) –4(2y – 0,9) + 2,4 = 5,6 – 10y;
–8y + 3,6 + 2,4 = 5,6 – 10y;
–8y + 10y = 5,6 – 6;
2y = –0,4;
y = –0,2.

Відповідь: –0,2.

Номер 50Номер 51Номер 52Номер 53Номер 54Номер 55Номер 56Номер 57Номер 58

Зворотній зв’язок